Guns and rubles : the defense industry in the Stalinist state - Harrison, Mark, 1949- (Yale-Hoover series on Stalin, Stalinism, and the Cold War., 2008)
Previously unknow details about Stalin's command system come to light in this book, as do fascinating insights into the relations between Soviet public and private sectors. Focusing on various aspects of the defence industry, this volume uncovers information on the inner workings of Stalin's dictatorship.